"When you mix the best of high society with the best of high society": culinary cannabis and the US hospitality industry. Issue 2 (4th May 2022) - Seaman, Alana N
ABSTRACT: The culinary use of cannabis in the US has increased dramatically in the wake of relaxed federal and state laws governing the production, distribution, possession and use of it and its derivatives. While cannabis refers to both hemp and marijuana — both of which produce the chemical compound cannabidiol (CBD) — only marijuana contains delta-9 tetrahydrocannabinol (THC), the psychoactive ingredient traditionally associated with its illicit use. Despite the distinction between the two types of plants and the chemicals that they are prized for creating, edible cannabis, due in part to repeated depictions in popular culture, has long been synonymous with cheap, box-mix, "pot" brownies made by a stereotypical on-screen stoner. Thus, stigmas surrounding its use persist. However, cannabis is becoming increasingly prized for its culinary uses and gastronomic profiles. The changing perceptions, legality and array of available strains of cannabis, as well as the resulting interest in its gastronomy, will no doubt have a significant impact on the American hospitality industry. This article clarifies the term "culinary cannabis" to describe the non-problematic use and/or enjoyment of hemp and/or marijuana (or ingredients derived from the two plant species) in food. It also speculates as to how the trend of culinary cannabis may impact the hospitality industry and identifies avenues for future research.